Gastrointestinal Bleeding as a Complication of Serial Transverse Enteroplasty - Fisher, Jeremy G. (J Pediatr Surg, 2014)
PURPOSE: Serial transverse enteroplasty (STEP) lengthens and tapers bowel in patients with intestinal failure and has a generally low complication profile. Evaluation and treatment of serious gastrointestinal bleeding (GIB) in three STEP patients is described. METHODS: Records of patients participating in an interdisciplinary intestinal rehabilitation program were reviewed to identify those who underwent STEP and had GIB necessitating red blood cell transfusion. RESULTS: Of 296 patients, 23 underwent STEP and 3 (13%) had subsequent GIB requiring transfusion. Underlying diagnoses were multiple atresias/intrauterine volvulus, gastroschisis, and gastroschisis with volvulus. STEP was performed at ages ranging from 3–5 months, using 3–8 stapler firings with an increase in mean bowel length from 23 to 45 cm. GIB was noted at 10–33 months post-op and resulted in 2–7 transfusions per patient over a period of 3–16 months. Gastrointestinal endoscopic evaluation demonstrated ulcers adjacent to the staple lines in two patients. Both had improvement of GIB with enteral antibiotics, sulfasalazine, topical enteral steroids and, ultimately, a period of bowel rest. The third patient had histological evidence of eosinophilic enteritis and was treated sequentially with antibiotics, sulfasalazine, enteral steroids, and an elemental diet. In all three, hemoglobin levels improved despite persistent occult bleeding. CONCLUSIONS: Significant GIB is a potential late complication of STEP. Endoscopy identified the underlying source of GIB in all three patients. A combination of enteral antibiotics, anti-inflammatory medications, and bowel rest was effective in the treatment of post-STEP GIB, without the need for additional bowel resection.